Development and evaluation of a booklet on dietary guidelines and menus for pregnant women in Sri Lanka - A. M. N. T. Adikari; R. Sivakanesan; D. G. N. G. Wijesinghe; C. Liyanage (Tropical Agricultural Research, 2019)
The improvement of nutrient intake during pregnancy by providing knowledge through dietary menus is not available in Sri Lanka. Hence, the purpose of this study was to develop a booklet of dietary-guidelines for pregnant women. Available dietary-guidelines and menus in Sri Lanka were gathered by reviewing the literature, following available recipes from recipe books and the internet, home visits, face-to-face interviews and through telephone calls. Further, a focus group survey was conducted to identify commonly consumed foods and menus. Nutritionally-balanced dietary menus were formulated and the nutrient content was calculated. The nutrient requirements of pregnant mother’s portion sizes were determined and menus were presented with portions. The content validity and format of the draft booklet were read by experts in the field of nutrition and dietetics to ensure the messages were right and could be read easily. The developed booklet was evaluated by fifteen pregnant-women for endusers’ satisfaction. The end-users responded that the maternal-nutrition information presented in the booklet was simple and easy to understand. The developed booklet can serve as an important source of information to improve the nutrient intake of pregnant women in Sri Lanka.